Digital communication strategy for public campaign to prevent stunting in Medan - Tenerman; Yenni, Elvita; Sari, Mila Trisna; Hajar, Siti (Jurnal Studi Komunikasi, 2025)
Medan City is one of the regions with significant stunting reduction achievements, from 19.9% ​​in 2021 to 5.8% in 2023. This achievement demonstrates the success of various intervention programs. However, the effectiveness of public communication, particularly through digital media, still requires in-depth evaluation to ensure that stunting prevention messages are truly understood and internalised by the target group. This study aims to analyse digital communication strategies for public stunting prevention campaigns in Medan City, Sumatra, Indonesia. The research method used is a mixed method with quantitative analysis through SEM-PLS and qualitative analysis through content analysis of digital campaigns. The results show that digital communication through social media can expand the reach of information, enhance interactivity, and strengthen public awareness of the importance of stunting prevention. However, the effectiveness of messages is still influenced by digital literacy, content relevance, and active audience involvement in the communication process.